Ex-Post impact assessment review of IFPRI’s research program on social protection, 2000–2012 - Nelson, Suzanne; Brown, Vicky; Presnall, Carrie; Downen, Jeanne; Frankenberger, Timothy R. (International Food Policy Research Institute, 2015)
IFPRI has conducted research on social protection (SP) issues since 2000, building on its earlier work on understanding the determinants of poverty and malnutrition and the linkages between them. The primary focus of the SP program was to (1) evaluate nutrition-related programs that address the underlying causes of malnutrition in order to improve the health and nutrition status of poor households; and (2) enlarge the knowledge base regarding the appropriate design for, and implementation and evaluation of, large-scale interventions for building human capital and reducing poverty.